Optimalisasi Supply Chain Management Guna Mengatasi Tantangan Persediaan Pada Industri Tape di Raja Tape Bondowoso - Puspita Arya Pangastuti; Hery Murnawan (Jurnal Serambi Engineering, 2024)
The level of competition in the ribbon industry is often discussed today because of the promising business opportunities for ribbons as a souvenir product typical of the town of Bondowoso. In addition, the decline in the availability of cassava raw materials since the Covid-19 pandemic has encouraged tape producers to search for raw materials of the highest quality, resulting in a mismatch between raw material sourcing and demand levels. Raja Tape is one of the MSMEs operating in the food sector in Bondowoso, East Java. Raja Tape often experiences shortages of cassava raw materials. Often, yellow cassava supplies are taken to middlemen even though the price difference is different, resulting in an imbalance between supply and demand in the following period. After conducting observations and interviews with the owner of Raja Tape, the researchers identified supply chain management problems, the first of which was the shortage of yellow cassava raw materials. In addition, the supply chain flow of tape products, starting from raw materials, land requirements and seeds of raw material components needed to fulfil production. The results of this research identified the needs of each component in the tape supply chain, namely land area and cassava, banana and bamboo tree seeds. This was done to determine the optimal requirements for tape supply at Raja Tape